Exposure of perfluorohexane sulfonate alters platelet homeostasis: From epidemiological evidence to mechanistic insights - Juxiao Li; Yue Luo; Xinrong Guo; Wenzheng Zhuo; Li Li; Ming Shi; Juan Ma; Lining Xu; Jiahuang Qiu (Ecotoxicology and Environmental Safety)
Increasing evidence indicates that traditional poly- and perfluoroalkyl substances (PFAS) may affect platelet function. However, the impact of mixed PFAS exposure on platelets and the specific contributions of each chemical remain unclear. Furthermore, the potential mechanisms involved are largely unknown. Using a combined experimental and epidemiological approach, this study comprehensively evaluated the relationship of PFAS with platelet levels and explored potential mechanisms. Serum concentrations of eight PFAS chemicals and complete blood counts were measured among 7860 adults in a population-based study. Multi-pollutant analysis models showed that PFHxS had the largest negative weight in mixed PFAS exposure with platelet counts. After adjusting for the false discovery rate and potential confounders, a significantly negative association was found between PFHxS and platelet counts (β = −11.27, 95 % CI: −14.86, −7.68). In contrast, no substantial association was observed between the other PFAS with higher concentrations and platelet counts. Therefore, we administered PFHxS orally to mice and found that this led to a rapid decrease in platelet counts. Further in vivo studies showed that PFHxS exposure resulted in a 22 % decrease in the number of megakaryocytes (MKs) in the bone marrow, where MKs were more inclined to remain in the early stage. RNA-sequencing indicated that PFHxS inhibited key signaling pathways involved in polyploidy regulation in bone marrow MKs, obstructing MK differentiation and maturation. Integrating experimental and epidemiological evidence, our findings indicate that PFHxS has the most significant impact on reducing platelet counts among all measured PFAS by inhibiting the maturation process of MKs.